2004
DOI: 10.1002/rcm.1388
|View full text |Cite
|
Sign up to set email alerts
|

The formation of complexes by tetraethylresorcarene with planar guest ions studied by electrospray ionisation Fourier transform ion cyclotron resonance mass spectrometry

Abstract: Resorcarenes have become a popular subject of study in the field of supramolecular chemistry. In this work the formation of host-guest complexes between a synthetic macrocyclic host, tetraethylresorcarene, and various eligible planar guests, was studied by mass spectrometric methods. The size and nature of the guest ion strongly influenced the complex formation. Collision-induced dissociation experiments revealed the fragmentation patterns of the resorcarene skeleton and the differences in fragmentation induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…In the gas phase, the ions probably lost a proton from one of the ammonium groups to decrease the repulsion between the two charged sites, and for that reason only singly charged species were observed. Similar behavior in MS measurements has been observed previously 26…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In the gas phase, the ions probably lost a proton from one of the ammonium groups to decrease the repulsion between the two charged sites, and for that reason only singly charged species were observed. Similar behavior in MS measurements has been observed previously 26…”
Section: Resultssupporting
confidence: 90%
“…In earlier studies, 26 unsubstituted tetraethyl resorcarene was not observed to form complexes with the oxidized forms of p-phen and o-phen. This underlines the importance of tosylium substituents in the complexation of resorcarene 1, in line with the observations made in our study of the complexation of aliphatic ammonium ions.…”
Section: Complex Formationmentioning
confidence: 90%
See 1 more Smart Citation
“…The non-covalent interactions within these host-guest complexes require a gentle ionisation method like ESI mass spectrometry, whose results are assumed to reflect the situation in solution [62]. By this method the complexation of resorcarenes with protonated aliphatic amines was shown to occur readily [63].…”
Section: Resorcarenes and Neutral Moleculesmentioning
confidence: 99%